ILMU SOSIAL DI INDONESIA: PELUANG, PERSOALAN DAN TANTANGAN - Achwan, Rochman (Jurnal Masyarakat dan Budaya, 2010)
Social science in Indonesia has enjoyed the luxury that has never been experienced in modern scientific history in the country. Nonetheless, this luxury has not been able to trail the development of social sciences achieved by neighboring countries. Using the concepts of social science’s types, this article concludes that the development of professional social science and critical social science has far left behind the development of public and policies related social science. This disparity actually marked the poor-quality of our social science development. This writing also recommends the needs to construct national social science by focusing on the revitalization of scientific association and reorientation of the method of social scientist’s thinking. By the time these steps are taken, Indonesian social scientists will be able to develop theories, concepts, and appropriate methodology within the contexts of Indonesian society. The national social science will become the amalgamation of Western social theories with local societal context. Keywords: social science development, Indonesia, revitalization of scientific association, reorientation of social science method